Identity Crisis among Adolescents in India: A Study - Bibori Baglary, Nabanita Das (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
Adolescent is a period of growth and development between childhood to adulthood. It is a phase of rapid development of physical, emotional, social development and mental functions such as abstract and concrete thinking, decision making and problem-solving skills, creativity is also developed fully during this adolescent period. But in some point of life adolescents passes through different stages and got stuck of their own identity and arise the confusion which termed as Identity Crisis or Role Confusion. Identity crisis means an identity to identify one’s self or personality and one’s social role how an individual performs in the society. Role confusion can also be said as personal, psychological and social conflict which occurs by different factors. To overcome various factors, there should have a proper guidance, open communication with the parents, teachers and dear ones. So that an individual would not find confusion about one’s self. In this research paper the researcher will discuss the fifth stage of Identity Crisis or Role Confusion of psychosocial development given by Erik Erikson and how role confusion arises in human being’s life and what are the solution to overcome role confusion and become a healthy personality. The data is collected through secondary sources i.e., research paper, article, thesis, journal, books etc.